Direct determination of 3-chloro-1, 2-propanediol esters in beef flavoring products by ultra-performance liquid chromatography tandem quadrupole mass spectrometry. Issue 114 (5th December 2016) - Chai, Qingqing; Zhang, Xiaoming; Karangwa, Eric; Dai, Qingyuan; Xia, Shuqin; Yu, Jingyang; Gao, Yahui
Abstract : A sensitive UPLC-TQ-MS method coupled with amino solid-phase extraction was developed for direct determination of 3-MCPD esters in the natural beef flavoring products. This method was evaluated in terms of linearity, repeatability and sensitivity. Abstract : A sensitive ultra-performance liquid chromatography tandem quadrupole mass spectrometry (UPLC-TQ-MS) method coupled with amino solid-phase extraction was developed for the direct determination of 3-chloro-1, 2-propanediol (3-MCPD) esters which were firstly detected in the natural beef flavoring products. The analyzed 3-MCPD esters in this paper contain three monoesters and six diesters. The validation data indicated that the proposed method provided good linearity, repeatability and sensitivity. The method showed a good linearity within the range of 40–200 μg kg −1 for monoesters and 20–100 μg kg −1 for diesters with the determination coefficients ( R 2 ) ranging from 0.9912 to 0.9993. The limits of detection (LODs) for monoesters and diesters of 3-MCPD were in the range of 0.04–5.0 μg kg −1 and 0.13–16.0 μg kg −1, respectively. The method accuracy was confirmed by higher sample recovery which ranged from 80.5 to 113.7%. The repeatability expressed as intra-day precision ranged from 0.8 to 9.9% and inter-day precision varied from 2.8 to 13.8%. The validated method was successfully applied for determination of 3-MCPD esters in beef flavoring products.